The ratio between the intestine length and the body length in Salmo ohridanus Steindachner from Ohrid Lake - Katerina Belichovska, Daniela Belichovska, Vasil Kostov (Faculty of Agricultural sciences and Food, University Ss. Cyrikl and Methodius in Skopje, 2016)
With the aim to investigate the relationship between the intestine length and the body length od Ohrid belvica (Salmo ohridanus, Steindachner, 1892), investigations were conducted on individuals captured in vegetative and reproductive development period of belvica, on three localities of Ohrid Lake: Kalista, Kaneo and Elesec, on depth from 45 to 70 m. Samples for researching have average body mass from 90 to 100 g and average total body length from 217 to 225 mm. It was found that this ratio varies from 0.73 to 0.98 for the three localities during the two developmental stages, or that is an average of 0.80 to 0.89. It has been established that the differences between the intestine length and the absolute body length, such as between localities and between the stages of development of Ohrid belvica are small and statistically insignificant. According to the results of the ratio between the intestine length and the body length, Ohrid belvica belongs to the group of zoophagous or carnivores.
Keywords: Ohrid belvica (Salmo ohridanus); intestine length; body length